Nanoprodrugs encapsulated with mesoporous silica nanoparticles for combined with photothermal therapy for the treatment and care of gastric cancer. (1st November 2022) - Jin, Qiaoli; Pan, Qin
Abstract: In this study, mesoporous silica nanoparticles (MSNs) were surface-modified with polymer poly(HEMA-co-PEGMA via surface-initiated atom transfer radical polymerization and a multifunctional nanoplatform MSNP@poly(HEMA-co-PEGMA-g-doxorubicin (DOX)/Rhodamine 6 G (R6G) was developed to combine photothermal (PTT) and chemotherapy therapy effectively. PTT induced by near-infrared (NIR) radiations might further destroy gastric cancer cell lines while the small-dye molecule was co-loaded into the MSNP pores. A 65 % higher cumulative drug release over 50-h occurs when the cis-aconitic anhydride link breaks under low-pH stimulation (typical physiological environment). High temperatures accelerated reversible covalent bond breakage. The accumulative release of the drug increased by 24.3 %, illustrating that higher temperatures can decrease the time needed to complete blood drug concentrations by 24.3 %. More than 90% of gastric tumour cells were destroyed after 48 h following exposure to NIR light irradiation with the prodrug delivery system, compared to DOX alone in vitro cytotoxicity tests. Because of this, rapidly reversible chemical bond breaking and photothermal activity in MSNP@poly(HEMA-co-PEGMA-g-DOX/R6G) increased the synergic impact of the chemotherapy, which offers tremendous promise in combination with the treatment and care of gastric cancer therapy.